BROADCASTING: AN ALTERNATIVE TO SUPPORT SPEAKING SKILL ACHIEVEMENTS - Masriatus Sholikhah (STKIP PGRI Jombang, 2016)
This present research is aimed to know the implementation of broadcasting technique towards students speaking skill achievements. Due to the low English speaking score, less motivation and limited English vocabulary acquire, this research is conducted by employing a project based learning method to overcome those problem faced by the students of 2014. The students are given a project to make a video broadcasting in which they are divided into some small group which consists of three students; this research is conducted in two cycles.The theory of Kemmis and McTaggart (2000) is employed to reveal the question of how the implementation of project based learning with broadcasting can significantly improve students speaking skill achievements. In addition, the result of cycle one show the students score is not significantly achieve the expected score based on the criteria of success standard. Further, this research is conducted to the following cycle, in this cycle 2 students showed the change. There are 82% students who attain the minimal score of criteria of success and 18% students who reach the bottom score of 78 point. As the result, the implementation of broadcasting technique is significantly improving students speaking achievement.